Formula Feeding Predisposes Neonatal Piglets to Clostridium difficile Gut Infection. (1st November 2017) - Grześkowiak, Łukasz; Martínez-Vallespín, Beatriz; Dadi, Temesgen H; Radloff, Judith; Amasheh, Salah; Heinsen, Femke-Anouska; Franke, Andre; Reinert, Knut; Vahjen, Wilfried; Zentek, Jürgen; Pieper, Robert
Abstract: Spontaneous outbreaks of Clostridium difficile infection (CDI) occur in neonatal piglets, but the predisposing factors are largely not known. To study the conditions for C. difficile colonization and CDI development, 48 neonatal piglets were moved into isolators, fed bovine milk–based formula, and infected with C. difficile 078. Analyses included clinical scoring; measurement of the fecal C. difficile burden, toxin B level, and calprotectin level; and postmortem histopathological analysis of colon specimens. Controls were noninfected suckling piglets. Fecal specimens from suckling piglets, formula-fed piglets, and formula-fed, C. difficile –infected piglets were used for metagenomics analysis. High background levels of C. difficile and toxin were detected in formula-fed piglets prior to infection, while suckling piglets carried about 3-fold less C. difficile, and toxin was not detected. Toxin level in C. difficile –challenged animals correlated positively with C. difficile and calprotectin levels. Postmortem signs of CDI were absent in suckling piglets, whereas mesocolonic edema and gas-filled distal small intestines and ceca, cellular damage, and reduced expression of claudins were associated with animals from the challenge trials. Microbiota in formula-fed piglets was enriched with Escherichia, Shigella, Streptococcus, Enterococcus, and Ruminococcus species. Formula-fed piglets were predisposed to C. difficile colonization earlier as compared to suckling piglets. Infection with a hypervirulent C. difficile ribotype did not aggravate the symptoms of infection. Sow-offspring association and consumption of porcine milk during early life may be crucial for the control of C. difficile expansion in piglets. Abstract : This study demonstrates that formula feeding predisposes neonatal piglets to intestinal dysbiosis and favors Clostridium difficile colonization earlier than observed in suckling piglets. Infection with a hypervirulent C. difficile strain does not aggravate the symptoms of infection. The repertoire of different maternal and environmental factors seems to set the conditions for disease development.